2022
DOI: 10.34160/jkds.2022.12.1.004
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors Associated with Achieving Oral Intake in Patients with Dysphagia

Abstract: Objective: The purpose of this study was to determine oral intake predictors, including videofluoroscopic swallow study (VFSS) and Charlson Comorbidity Index (CCI), in patients with diseases/conditions requiring nasogastric (NG) tube feeding for dysphagia. Methods: We retrospectively extracted the clinical or radiological medical records of 501 patients with internal medicine diseases who were referred for VFSS to evaluate dysphagia between January 2012 and August 2021. Our study analyzed 310 (61.9%) subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…[19] Stroke and aspiration pneumonia are known as important clinical factors that make the removal of NG tubes difficult. [20] In patients with stroke and dysphagia, functional status was a significant clinical factor in nasogastric tube removal. [16] In a large-scale study that aimed to identify factors predicting oral intake in elderly patients with aspiration pneumonia, it was found that not only functional status but also underweight was an important factor in the delayed initiation of oral intake.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[19] Stroke and aspiration pneumonia are known as important clinical factors that make the removal of NG tubes difficult. [20] In patients with stroke and dysphagia, functional status was a significant clinical factor in nasogastric tube removal. [16] In a large-scale study that aimed to identify factors predicting oral intake in elderly patients with aspiration pneumonia, it was found that not only functional status but also underweight was an important factor in the delayed initiation of oral intake.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Several studies have investigated various approaches to identify clinical factors related with successful transition from tube feedings to oral feedings. [13][14][15][16][17][18][19][20][21] Younger age was associated with a successful transition to oral nutrition from gastrostomy tube feeding in adults diagnosed with cancer. [19] Stroke and aspiration pneumonia are known as important clinical factors that make the removal of NG tubes difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation